Possible risk factors of sinus membrane perforation during sinus floor elevation: A retrospective study (Annals of Medical Research, 2021)
Aim: To investigate risk factors causing sinus membrane perforation during sinus floor elevation (SFE) performed with lateral windowtechnique and to evaluate the sinus membrane health after SFE via Cone-Beam Computed Tomography (CBCT).Materials and Methods: CBCT images of 33 patients with sinus membrane perforation during SFE and 33 patients without perforationduring SFE as a control and a total of 80 CBCTs were evaluated. Patient-related factors (age, sex, smoking) and maxillary sinus-related factors (preoperative membrane thickness, residual bone thickness, postoperative membrane thickness, and postoperative total bone thickness, type of sinus membrane morphology, and presence of septa) were assessed.Results: Preoperative sinus membrane thickness of the perforated group (4.38 ± 6.02 mm) was significantly higher than the non-perforated group (1.74 ± 2.81 mm) (p = 0.02). No significant difference was found between preoperative and postoperative membranethicknesses of the non-perforated and perforated group (p = 0.135 and p = 0.106, respectively). The perforation rate was highest (83.3%) in the group of mucosal thickness ≥4 mm. Membrane perforation was observed in 100% of circumferential and complete type sinus membrane morphology, 80% of polyp type morphology, and 85.7% in irregular type morphology. A relationship was found between the presence of septa and membrane perforation (p = 0.01).Conclusion: The study results show that the presence of septa, age of >55 years, and a sinus membrane thickness of >4 mm are associated with an increased risk of sinus membrane perforation. Perforation did not affect postoperative sinus membranethickness.